JENIS-JENIS SEMUT ARBOREAL (HYMENOPTERA: FORMICIDAE) DI KAWASAN KAMPUS UNIVERSITAS TANJUNGPURA DENGAN TIGA METODE KOLEKSI - Indrianasari, Melvy; Kustiati, Kustiati; Saputra, Firman (Universitas Tanjungpura, 2020)
Ants as insects occupy various habitats and ecological niches. Universitas Tanjungpura is an area with variable vegetation physiognomies that has the potential to have a lot of ant microhabitat. This study aims to determine the most effective method for collecting arboreal ants (Hymenoptera: Formicidae) found in the campus area of Universitas Tanjungpura. The study was conducted from August 2018 to February 2019 at ten locationsÂ based on their environmental condition. Ants were collected in three different methods: hand collecting, bait traps, and yellow pan traps. There were 39 species of Formicidae collectedfromall locations. These results were obtained by hand collecting (32 species), bait traps (32 species), and yellow pan traps (4 species). Hand collecting and bait traps are the most effective method for collecting arboreal ants in Universitas Tanjungpura.